PERMODELAN BIAYA KEMACETAN PENGGUNA MOBIL PRIBADI DENGAN VARIASI NILAI KECEPATAN AKTUAL KENDARAAN - Sugiyanto, Gito (Jurnal Transportasi, 2012)
Traffic congestion is a situation when the actual speed of the vehicle is under the free flow speed. This situation resulted in losses for road users, which can be an increase in fuel consumption, time wasted, and environmental pollution. The purpose of this study is to develop a model for the congestion charge for private car users for a variety of time values and the actual vehicle speed in the corridor of Jalan Malioboro, Yogyakarta. Congestion charge is the difference between the generalized transportation cost on the free flow speed condition and the generalized transportation cost on the actual speed condition. The generalized transportation cost consists of vehicle operating costs, travel time costs, and the pollution cost. This study found that the cost of congestion for private car users in Malioboro, Yogyakarta, for respondents with a trip to the Malioboro as a destination is IDR 4,009.15 / trip and for through traffic respondents is IDR 4,224.29/trip. Moreover, the congestion cost model for private car users in Malioboro corridor is an exponential function.Keywords: congestion cost, generalized cost, actual speed, free flow speedAbstrak